Two temperate corals are tolerant to low pH regardless of previous exposure to natural CO2 vents. Issue 11 (1st October 2021) - Carbonne, Chloe; Teixidó, Núria; Moore, Billy; Mirasole, Alice; Guttierez, Thomas; Gattuso, Jean‐Pierre; Comeau, Steeve
Abstract: Ocean acidification is perceived to be a major threat for many calcifying organisms, including scleractinian corals. Here, we investigate (1) whether past exposure to low pH environments associated with CO2 vents could increase corals tolerance to low pH and (2) whether zooxanthellate corals are more tolerant to low pH than azooxanthellate corals. To test these hypotheses, two Mediterranean colonial corals Cladocora caespitosa (zooxanthellate) and Astroides calycularis (azooxanthellate) were collected from CO2 vents and reference sites and incubated in the laboratory under present day (pH on the total scale, pHT 8.07) and low pH conditions (pHT 7.70). Rates of net calcification, dark respiration, and photosynthesis were monitored during a 6‐month experiment. Monthly net calcification was assessed every 27–35 d using the buoyant weight technique, whereas light and dark net calcification was estimated using the alkalinity anomaly technique during 1‐h incubations. Neither species showed any change in net calcification rates, respiration, and photosynthesis regardless of their environmental history, pH treatment, and trophic strategy. Our results indicate that C. caespitosa and As. calycularis could tolerate future ocean acidification conditions for at least 6 months. These results will aid in predicting species' future responses to ocean acidification, and thus improve the management and conservation of Mediterranean corals.